Magnetic Nanoparticle‐Mediated Gene Delivery to Two‐ and Three‐Dimensional Neural Stem Cell Cultures: Magnet‐Assisted Transfection and Multifection Approaches to Enhance Outcomes. (2nd February 2017) - Pickard, Mark R.; Adams, Christopher F.; Chari, Divya M.
Abstract: Neural stem cells (NSCs) have high translational potential in transplantation therapies for neural repair. Enhancement of their therapeutic capacity by genetic engineering is an important goal for regenerative neurology. Magnetic nanoparticles (MNPs) are major non‐viral vectors for safe bioengineering of NSCs, offering critical translational benefits over viral vectors, including safety, scalability, and ease of use. This unit describes protocols for the production of suspension (neurosphere) and adherent (monolayer) murine NSC cultures. Genetic engineering of NSCs with MNPs and the application of 'magnetofection' (magnetic fields) or 'multifection' (repeat transfection) approaches to enhance gene delivery are described. Magnetofection of monolayer cultures achieves optimal transfection, but neurospheres offer key advantages for neural graft survival post‐transplantation. A protocol is presented which allows the advantageous features of each approach to be combined into a single procedure for transplantation. The adaptation of these protocols for other MNP preparations is considered, with emphasis on the evaluation of procedural safety. © 2017 by John Wiley & Sons, Inc.